2010
DOI: 10.1029/2010jd014435
|View full text |Cite
|
Sign up to set email alerts
|

Highly nonlinear ozone formation in the Houston region and implications for emission controls

Abstract: [1] Photochemical modeling with high-order sensitivity analysis is applied to simulate the nonlinear responses of ozone to NO x and VOC emissions from different source regions in the Houston-Galveston-Brazoria area and their interactions. First-order responses of daytime ozone to Houston NO x emissions are typically positive but are negative in the core region, indicating a NO x -inhibited chemical regime there. Houston anthropogenic VOC emissions exert a spatially smaller impact on ozone but are important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…In this SIP, random industrial emission events were addressed with targeted controls, and the regulatory model was used to formulate policy (e.g., NO x and HRVOC cap and trade programs, reductions of industrial NO x , mobile source reductions) for the remaining causes of violations. More recently, it has been suggested that peak O 3 may be responsive initially to targeted ship channel VOC emissions, but further O 3 reductions may require NO x limits (Xiao et al, 2010). This dual approach proved to be effective in reducing ozone and could be applied in current SIP efforts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this SIP, random industrial emission events were addressed with targeted controls, and the regulatory model was used to formulate policy (e.g., NO x and HRVOC cap and trade programs, reductions of industrial NO x , mobile source reductions) for the remaining causes of violations. More recently, it has been suggested that peak O 3 may be responsive initially to targeted ship channel VOC emissions, but further O 3 reductions may require NO x limits (Xiao et al, 2010). This dual approach proved to be effective in reducing ozone and could be applied in current SIP efforts.…”
Section: Resultsmentioning
confidence: 99%
“…These emissions are random, and, although rare at any one facility, due to Houston's massive industrial network, there were more than 1000 releases reported in 2003 (Murphy and Allen, 2005). Immediately after a release, modeling and observational evidence suggest an initial period of rapid O 3 formation that results in a spatially limited downwind plume of high O 3 (Henderson et al, 2010;Kleinman et al, 2002;Ryerson et al, 2003;Xiao et al, 2010). One study found that targeted episodic HRVOC emissions from the ship channel can correct for low reactivity in models (Byun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We maximize NO x abatement by locating the study site south of Houston in an area already high in biogenic VOC emissions (74) where O 3 formation is expected to be mostly NO x limited-as it is in most of the HGB area (figure 2b in ref. 42) especially during late morning to late afternoon (42,62) when biogenic VOC emissions are highest. Thus, VOC emissions from the additional forest are unlikely to lead to additional O 3 formation that would reduce the O 3 net balance of the project.…”
Section: Case Study and Methodsmentioning
confidence: 99%
“…In general, ozone formation in urban areas tends to be initially limited by the availability of VOCs, while downwind ozone formation in rural areas is generally limited by the amount of NO x that is available for reaction (Sillman 1999). A noted reversal in this trend is the Houston Ship Channel, in which industrial emissions of highly-reactive VOCs (HRVOC) have led to spikes in urban ozone concentrations in a NO x -limited ozone formation regime (Daum et al 2003;Nam et al 2006;Xiao et al 2010). Within plumes from large power plants, the ozone chemistry tends to be more controlled by the availability of VOCs than surrounding ambient conditions (Sillman 1999) until the plume becomes fully mixed with the ambient atmosphere (Frost et al 2006).…”
Section: Ground Level Ozone Formationmentioning
confidence: 99%
“…(Alhajeri et al 2011a) Over the last several decades, cap and trade programs such as the Acid Rain Program for sulfur dioxide emissions (SO 2 ) (Burtraw et al 1999) and the NO x State Implementation Plan (Alhajeri et al 2011a) at comparable cost to other emissions controls (Alhajeri 2012;Sun et al 2012). Ozone responses to changes in NO x emissions are highly non-linear (Sillman 1999) and can differ regionally (Nobel et al 2001;Mauzerall et al 2005) and even within a single urban area (Daum et al 2003;Xiao et al 2010 compares the application of a seasonal NO x emissions price to an emissions price that is only imposed on predicted high ozone days when marginal health impacts (Gryparis et al 2004, Mauzerall et al 2005) and regulatory concerns would be elevated. ERCOT is an interesting test-bed for examining the potential impacts of a NO x emissions market based on air quality forecasting since the state has a relatively self-sufficient electric grid and large in-state production of natural gas and coal, leading to a diverse portfolio of generation options that are representative of the nation as a whole (Grubert et al 2012).…”
Section: Introductionmentioning
confidence: 99%